SOCIOLOGICAL ASPECTS OF WORKING WITH LONELY OLDER ADULTS (American Journal of Research in Humanities and Social Sciences, 2026)
The phenomenon of loneliness among older adults has become one of the most urgent socio-gerontological issues in modern society. Population ageing, the transformation of family relations, migration, urbanization, retirement, health limitations, and digital inequality have significantly changed the social position of elderly people. Loneliness in old age is not only an emotional or psychological condition but also a complex social phenomenon connected with weakening social ties, loss of social roles, limited participation in community life, and insufficient institutional support. This article analyzes the sociological aspects of working with lonely older adults from the perspective of social integration, social capital, intergenerational solidarity, community-based care, and social policy. The study emphasizes that effective work with lonely elderly people requires a systematic approach involving family, community, healthcare institutions, social services, non-governmental organizations, and state policy. The article argues that loneliness among older adults should be understood as a form of social vulnerability and potential social exclusion, and therefore it must be addressed through preventive, inclusive, and humanistic mechanisms of social support.